The Degree to Which the International Standards of Media and Information Literacy are Included in the Textbooks of Social Studies of Basic Education in Jordan: An Analytical Study - Shaltaf, Ola Badreddin; Als’aideh, Monem Abdul Karim (Dirasat: Educational Sciences, 2025)
Objectives: This study aimed to determine the extent to which global standards for media and information literacy are included in the social studies textbooks for the basic education stage in Jordan. Methods: The study was based on the analytical method (content analysis). The researcher designed the tool based on the standards of the UNESCO document Global Standards for Media and Information Literacy Curricula Development Guidelines and derived the outcomes that meet the standards. Results: The study concluded that these standards were not fully achieved in the social studies textbooks for the basic education stage in Jordan. The fourth standard was the most frequently mentioned, which states: "Identify and evaluate websites with useful content to meet personal, educational, political, cultural, religious, and other community needs." The fifteenth standard, which states: "Manage interactions with educational or educational games, especially when using artificial intelligence in them," was the least frequently mentioned. Some outcomes were achieved with few repetitions, which does not fully meet the standard, while some standards were not mentioned at all in the textbooks. conclusions: The study recommended the need to integrate international media literacy standards in a balanced way in social studies textbooks due to the importance and necessity of these standards.